Financial reporting in Japan - Ballon, Robert J. (Kodansha International, 1976)
This is a research on how corporate financial reporting practices are influenced by such environmental (to accounting) factors as the capital market institutions, the legal system and management behavior. International comparison provides an appropriate setting.